Heteroatom‐Doped Carbon Materials: Synthesis, Mechanism, and Application for Sodium‐Ion Batteries. Issue 4 (8th October 2018) - Chen, Weimin; Wan, Min; Liu, Qing; Xiong, Xiaoqin; Yu, Faquan; Huang, Yunhui
Abstract: Sodium‐ion batteries (SIBs) show promising application in large‐scale energy storage as future alternatives to lithium‐ion batteries. Carbonaceous materials are attractive anode candidates for SIBs due to low cost, abundance, and high safety. In general, doping heteroatoms such as N, B, O, S, and P in carbon‐based materials gives rise to high electronic mobility, good sodium mobility, and enhanced capacity, showing a great potential in sodium storage. This review summarizes the recent progress in the design, synthesis, and electrochemical properties of heteroatom‐doped carbon anodes, including one‐element doped carbons and several‐elements codoped carbons, aiming to help the readers comprehensively learn how to fabricate heteroatom‐doped carbons and use them in SIBs. Additionally, the advantages, mechanism, critical issues, and possible solutions of heteroatom‐doped carbons are discussed and the future research trends are proposed. This will provide a deep insight into the development of SIBs anode materials. Abstract : This review summarizes the synthetic strategies and the applications in sodium‐ion batteries for sole‐element B‐, N‐, S‐, and P‐doped, dual‐elements doped, and triple‐elements doped carbon materials. The mechanisms of improved performances for carbonaceous materials by heteroatom doping are also discussed. The advantages, challenges, and possible solutions for application of heteroatom‐doped carbons are discussed, and the future research areas are suggested.